Did Europe Move in the Right Direction on E‐waste Legislation?. Issue 1 (9th July 2018) - Mazahir, Shumail; Verter, Vedat; Boyaci, Tamer; Van Wassenhove, Luk N.
Abstract : This study presents an analytical framework of the product take back legislation in the context of product reuse. We characterize existing and proposed forms of E‐waste legislation and compare their environmental and economic performance. Using stylized models, we analyze an OEM's decision about new and remanufactured product quantity in response to the legislative mechanism. We focus on the 2012 waste electrical and electronic equipment directive in Europe, where the policy makers intended to create additional incentives for the product reuse. Through a comparison to the Original 2002 version of the directive, we find that these incentives translate into improved environmental outcomes only for a limited set of products. We also study a proposed policy that advocates a separate target for the product reuse. Our analysis reveals that from an environmental standpoint, the Recast version is always dominated either by the Original policy or by the one that advocates a separate target for product reuse. We show that the benefits of a separate reuse target scheme can be fully replicated with the aid of fiscal levers. Our main message is that there cannot be a single best environmental policy that is suitable for all products. Therefore, the consideration of product attributes is essential in identification of the most appropriate policy tool. This can be done either by the implementation of different policies on each product category or by implementation of product‐based target levels.